Sumbangan Pengenalan Waktu Tradisional “Pranata Mangsa” pada Pengelolaan Hama Terpadu - Sukardi Wisnubroto (Jurnal Perlindungan Tanaman Indonesia, 1998)
Cropping pattern and time of planting are two of several factors supporting Integrated Pest Management (IPM). Pranata Mangsa (PM) is a Javanese traditional time reckoning which has existed since some thousand years ago but formally as a calendar was socialized by the King of Surakarta in June 22, 1855. PM has twelve mangsas (similar to a month for other calendar system). Some farmers in Central Java, especially around Surakarta, still use this time reckoning system as a guidance for their activities including the agricultural ones. This system for example enables people to predict the beginning of wet and dry season and also to determine the best time for rice planting to escape from pests and diseases. Based on the information collected in Boyolali district, Central Java, it is known that there is a relationship between mangsa indicators with the attack intensity of rice stemborers.